CORONAVIRUSES: THERE AND BACK AGAIN - BRANDÃO, P. E.; GRAVINATTI, M. L.; SANTANA, N. F. C.; HORA, A. S. (Ars Veterinaria, 2020)
With the raise of SARS-CoV-2 in late 2019 and the associated COVID-19 pandemics, much of the knowledge gathered from decades on research on other coronavirus species that use humans and other animals as hosts is invaluable to help counteract the burden of this new disease. This review ais to bring the highlights on coronavirus Biology and the most frequent diseases they might cause, serving rather as an introduction to the field.